Regulasi Cryptocurrency dan Hak Asasi Manusia: Tinjauan Terhadap Hak Privasi, Keamanan, dan Kepemilikan Digital - Adisurya; Mochamad Mansur (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2023)
This study aims to evaluate the impact of cryptocurrency regulations on human rights, with a particular focus on digital rights, privacy, and security. Cryptocurrencies, such as Bitcoin and Ethereum, have rapidly evolved as a new form of decentralized digital finance. However, this growth has raised questions about how cryptocurrencies affect individuals' rights, especially in terms of privacy and the security of personal data. This study employs a normative legal approach and conceptual analysis to explore existing regulations and trends related to cryptocurrency in various jurisdictions. Additionally, the research incorporates a theoretical perspective on human rights to identify potential implications of cryptocurrency regulation on privacy and digital security. The study's findings should shed light on how human rights are affected by the way cryptocurrencies are currently regulated and set the stage for any future legislative adjustments that would be required to strike a balance between personal safety and technological innovation. This research can also assist policymakers and regulators in tightening legal work practices, which will enable advancements in cryptocurrency while upholding individual rights. With the continuous growth in cryptocurrency usage and the growing concerns about privacy and security, this study is relevant in supporting ongoing discussions on how the law can accommodate this innovative technology without compromising human rights.